Acceptance and commitment therapy for clients institutionalized for severe substance-use disorder: a pilot study - Svanberg G; Munck I; Levander M (Dove Medical Press, 2017)
Gabriella Svanberg,1 Ingrid Munck,2 Maria Levander3 1Department of Substance Abuse, The Swedish National Board of Institutional Care, Stockholm, 2Department of Education and Special Education, University of Gothenburg, Gothenburg, 3Department of Clinical Neuroscience, Karolinska Institute, Stockholm, Sweden Background: Individuals with substance-use disorder (SUD) often have co-occurring mental health disorders and decreased executive function, both of which are barriers to sustained rehabilitation. Clients with severe SUD can be institutionalized in The Swedish National Board of Institutional Care but are difficult to engage and dropout rates remain high. Recent studies suggest that acceptance and commitment therapy (ACT) is an effective treatment for mental health and SUD.Objectives: The overall aims of the present pilot study were to explore a manual-based ACT intervention for clients institutionalized for severe SUD and to describe the effects on mental health, psychological flexibility, and executive function. This pilot study is the first to use a manual-based ACT intervention within an inpatient context.Methods: Eighteen participants received a seven-session ACT intervention tailored for SUD. Statistical analyses were performed for the complete data (n=18) and on an individual level of follow-up data for each participant. In order to follow and describe changes, the strategy was to assess the change in 13 clinical scales from pre-intervention to post-intervention.Results: Results suggested that there was no change in mental health and a trend implying positive changes for psychological flexibility and for 9 of 10 executive functions (e.g., inhibitory control, task monitoring, and emotional control).Conclusion: The pilot study suggests clinical gains in psychological flexibility and executive functions both at the Institution regulated by the Care of Alcoholics and Drugabuser Act (also known as LVM home) and at the individual level. Since the sample size does not provide adequate statistical power to generalize and to draw firm conclusions concerning intervention effects, findings are descriptive and preliminary in nature. Further development and implementation of ACT on a larger scale study, including the maintenance phase and a follow-up, is needed. Keywords: acceptance and commitment therapy, substance-use disorder, psychological flexibility, executive function